Density Functional Theory Calculations of Magnesium Hydride: A Comparison of Bulk and Nanoparticle Thermodynamics - Buckley, A.; Carter, Damien; Sheppard, Drew; Buckley, Craig (American Chemical Society, 2012)
Density functional theory calculations have been performed on a range of magnesium and magnesium hydride nanoclusters to examine the 1 bar desorption temperatures. The vibrational entropies and enthalpies are calculated for each cluster, within the harmonic approximation, which permits calculation of the desorption Gibbs free energy of reaction. For the bulk system, good agreement is found with experiment for the desorption temperature and a range of structural and electronic properties. For the nanoparticulate systems, we report binding energies, along with desorption reaction entropies and enthalpies. The finite-temperature effects on the vibrational energies of all system sizes are examined, and the findings suggest that the harmonic approximation is too restricted to account for the experimentally observed reductions in the nanoparticulate reaction enthalpies.